Anti-flotillin-1/2 antibodies in a patient with neurogenic muscle atrophy and mild neuropsychological impairment - Tobias A. Wagner-Altendorf; Klaus-Peter Wandinger; Robert Markewitz; Anna Antufjew; Tobias Boppel; Thomas F. Münte (Neurological Research and Practice, 2022)
Abstract Autoimmune-mediated neural inflammation can affect both the central and the peripheral nervous system. Recently, antibodies against the peripheral membrane protein flotillin have been described in patients with multiple sclerosis, limbic encephalitis and sensorimotor demyelinating polyneuropathy. Here, we report the case of a 75-year-old male patient presenting with slowly progressive muscle weakness, as well as mild cognitive impairment. MR neurography of the leg showed fascicular enlargement and inflammation of ischiadic nerve fibers, while cerebral MRI showed bilateral hippocampal atrophy. Serological testing revealed positive anti-flotillin-1/2 antibodies in serum (1:100) and CSF (1:1). Assuming autoimmune anti-flotillin antibody-associated neurogenic muscle atrophy, the patient was treated with immunoglobulins, which led to a clinical improvement of muscle weakness. In light of the positive anti-flotillin antibodies and the local CNS immunoglobulin production, the mild cognitive impairment and hippocampal atrophy were interpreted as a cerebral involvement in the sense of a subclinical limbic encephalitis. We conclude that anti-flotillin antibodies can be associated with central and peripheral nervous system autoimmunity and should be considered in diagnostical workup.